Chromosomal replication incompatibility in Dam methyltransferase deficient Escherichia coli cells. - Løbner-Olesen, A (1996)
Dam methyltransferase deficient Escherichia coli cells containing minichromosomes were constructed. Free plasmid DNA could not be detected in these cells and the minichromosomes were found to be integrated in multiple copies in the origin of replication (oriC) region of the host chromosome. The absence of the initiation cascade in Dam- cells is proposed to account for this observation of apparent incompatibility between plasmid and chromosomal copies of oriC. Studies using oriC-pBR322 chimeric plasmids and their deletion derivatives indicated that the incompatibility determinant is an intact and functional oriC sequence. The seqA2 mutation was found to overcome the incompatability phenotype by increasing the cellular oriC copy number 3-fold thereby allowing minichromosomes to coexist with the chromosome. The replication pattern of a wild-type strain with multiple integrated minichromosomes in the oriC region of the chromosome, led to the conclusion that initiation of DNA replication commences at a fixed cell mass, irrespective of the number of origins contained on the chromosome.